Analisis Pengaruh Endorsement Influencer / Artis terhadap Penggunaan Judi Online pada Generasi Millennial atau Z di Media Sosial - Feilincya Gabriela; Ilman Akbar Effendi; Rossita Dewi (Mahesa Research Center, 2023)
In the current era of globalization, the rapid development of social media is evident. Social media functions not only as an online medium facilitating social connections but also strengthens relationships among users. The use of social media as a promotional tool is prevalent, particularly on platforms like Instagram and TikTok. However, it is crucial to note that the use of social media for promotional activities by artists or influencers can have a significant impact, especially on the millennial and Generation Z populations, particularly when endorsing products or services related to online gambling or illegal activities. This research aims to analyze the phenomenon of influencer endorsements and their association with the use of online gambling among millennials and Generation Z through social media. The research methodology employed is qualitative, utilizing data collection techniques such as interviews, observations, and documentation. The study participants consist of four individuals representing the millennial and Generation Z demographics. The research findings indicate that influencers have a substantial impact on influencing the interest of millennials and Generation Z in online gambling. Additionally, social media algorithms tend to display video advertisements promoting online gambling featuring these influencers. In conclusion, the influence of influencers and social media algorithms can significantly affect the attitudes and behaviors of millennials and Generation Z regarding online gambling endorsements.